2010
DOI: 10.1097/qai.0b013e3181c7d349
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of hA3G and hA3B mRNA Levels With HIV Disease Progression Among HIV-Infected Individuals of China

Abstract: Higher expression levels of hA3G and hA3B mRNA in the peripheral blood mononuclear cells of Chinese HIV-infected individuals were found to be associated with slower HIV disease progression, suggesting their potential roles in antiviral innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In agreement with this, several investigators reported that A3G expression levels correlate inversely with HIV-1 viral load and disease progression and directly with the mutational loads in the viral genome (Table 2). 234; 235; 236; 237; 238; 239 Interestingly, A3G mRNA levels are higher in long-term nonprogressors than in uninfected controls, while the lowest A3G mRNA levels are found in HIV progressors. 234 In a South African cohort, significantly higher A3G expression in PBMCs was shown for HIV-1-exposed seronegative individuals compared to HIV-1-seropositive patients or healthy controls, 240 but another recent study could not demonstrate any difference in the expression levels of A3G in HIV-1-exposed seronegative patients.…”
Section: A3 Restriction In Hiv-1 Infected Patientsmentioning
confidence: 96%
“…In agreement with this, several investigators reported that A3G expression levels correlate inversely with HIV-1 viral load and disease progression and directly with the mutational loads in the viral genome (Table 2). 234; 235; 236; 237; 238; 239 Interestingly, A3G mRNA levels are higher in long-term nonprogressors than in uninfected controls, while the lowest A3G mRNA levels are found in HIV progressors. 234 In a South African cohort, significantly higher A3G expression in PBMCs was shown for HIV-1-exposed seronegative individuals compared to HIV-1-seropositive patients or healthy controls, 240 but another recent study could not demonstrate any difference in the expression levels of A3G in HIV-1-exposed seronegative patients.…”
Section: A3 Restriction In Hiv-1 Infected Patientsmentioning
confidence: 96%
“…The greater viral survival advantage of APOBEC3G-Vif neutralization is suggested by the following: (i) APOBEC3G is more likely to generate stop codons than APOBEC3F and other deaminases (3,12), (ii) the processive single-stranded DNA scanning behavior of APOBEC3G ("jumping" and "sliding") increases its mutagenic potential relative to that of APOBEC3F (predominately "jumping") (80), (iii) most (81)(82)(83)(84)(85)(86) although not all (87) studies demonstrate that APOBEC3G expression levels correlate inversely with viral load and disease progression in adults, (iv) APOBEC3G expression levels are higher in long-term nonprogressors than in uninfected controls and lowest in rapid progressors (81), (v) APOBEC3G mRNA is expressed at higher levels than that of APOBEC3F in lymphocytes and lymphoid tissue (88,89), and APOBEC3F is not expressed in monocytes/macrophages and dendritic cells, whereas APOBEC3G is (71), (vi) APOBEC3F and other deaminases have little or no antiviral effect in primary cells or when expressed at similar levels in cell lines (68,69), although a cumulative antiviral effect of APOBEC3F, albeit less than that of APOBEC3G, was observed in a long-term (27 days) culture of lab-adapted virus in CD4 ϩ T cells and monocyte/macrophages (4), (vii) APOBEC3F has no significant effect on virus infectivity when stably expressed in HeLa cells, even though it was packaged into nascent virions (68), (viii) the protein expression levels of APOBEC3G are higher than those of APOBEC3F in peripheral blood mononuclear cells (PBMCs) from different donors, although the use of different antibodies precluded an accurate quantification of protein expression (69), and (viiii) APOBEC3G had a stronger antiviral effect than APOBEC3F when they were expressed as fusions with the FLAG-epitope at the same levels in cell lines (90). We acknowledge that there may be a discordance between mRNA and protein expression levels and antiviral effects and that these studies do not analyze the degree to which each APOBEC3 inhibits reverse transcription, stimulates cDNA degradation, or inhibits integration; however, these limitations do not challenge the conclusion that APOBEC3G activity is more deleterious to HIV survival than the activities of other deaminases (4).…”
Section: Figmentioning
confidence: 99%
“…It was further found that human APOBEC3B mRNA levels were higher in HIV-negative individuals and in slow progressors than in patients with AIDS, and that these levels were positively correlated with CD4 + T cell count and negatively correlated with HIV-1 viral load and disease progression among HIV-1-infected persons [8].…”
Section: Reply To Itaya Et Almentioning
confidence: 97%
“…Although early reports indicated that APOBEC3B is not expressed in lymphoid cells targeted by HIV [4,5], more recent studies have shown APOBEC3B mRNA expression in activated CD4 + T cells and lymphoid cells [6][7][8], although at expression levels that are 50% lower than those of either APOBEC3F or APOBEC3G [8]. It was further found that human APOBEC3B mRNA levels were higher in HIV-negative individuals and in slow progressors than in patients with AIDS, and that these levels were positively correlated with CD4 + T cell count and negatively correlated with HIV-1 viral load and disease progression among HIV-1-infected persons [8].…”
Section: Reply To Itaya Et Almentioning
confidence: 97%